2019
DOI: 10.1088/2631-7990/ab263f
|View full text |Cite
|
Sign up to set email alerts
|

Material embrittlement in high strain-rate loading

Abstract: Material embrittlement is often encountered in machining, heat treatment, hydrogen and lowtemperature conditions among which machining is strain-rate related. More strain-rate evoked embrittlement is expected in material loading processes, such as in high-speed machining and projectile penetration. In order to understand the fundamental mechanisms of the strain-rate evoked material embrittlement, this study is concerned with the material responses to loading at high strain-rates. It then explores the strain-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 124 publications
1
18
0
Order By: Relevance
“…For impact loading at a lower strain rate, the stress or strain threshold is higher, while at a higher strain rate, it become slower. In other words, the brain tissue, like other materials, may become more brittle at a higher strain rate ( Yang and Zhang, 2019 ). This is probably because micromechanically, there is not enough time for dispersion of the linear momentum into other regions of the brain, and the localized deformation is manifested through skull indentation and coup injury.…”
Section: Discussionmentioning
confidence: 99%
“…For impact loading at a lower strain rate, the stress or strain threshold is higher, while at a higher strain rate, it become slower. In other words, the brain tissue, like other materials, may become more brittle at a higher strain rate ( Yang and Zhang, 2019 ). This is probably because micromechanically, there is not enough time for dispersion of the linear momentum into other regions of the brain, and the localized deformation is manifested through skull indentation and coup injury.…”
Section: Discussionmentioning
confidence: 99%
“…The second, a number of researchers reported other theoretical perspectives compared with ductile regime grinding. Yang and Zhang [43] suggested that during ultrasonically assisted machining, the higher speed and acceleration led to a high strain rate, which might evoke material embrittlement in the machining process. Accordingly, the material resistance ahead of the crack tip increased with the strain-rate and impeded crack propagation as shown in Fig.…”
Section: Discussion On Ultrasonic Vibration Effectmentioning
confidence: 99%
“…In addition, the current contact constitutive model in DEM simulation basically only considers the mechanical response of the material under static or quasi-static (including the calibration process). But in the processing of hard-brittle materials, the strain rate of the material is usually up to 10 2 -10 7 s -1 [202]. Therefore, how to improve the constitutive model of the material and calibrate its dynamic response through experiments such as Split Hopkins Pressure Bar (SHPB) [203] may be a direction worth studying in the future of DEM numerical simulation processing of hard-brittle materials.…”
Section: Selection and Improvement Of Materials Constitutive Modelmentioning
confidence: 99%